Sandwich-Type Double-Layer Piezoelectric Nanogenerators Based on One- and Two-Dimensional ZnO Nanostructures With Improved Output Performance - Fakhri, Parisa; Eaianli, Naeimeh; Bagherzadeh, Roohollah; Jaleh, Babak; Kashfi, Mohammad; FAUSTO, RUI (Nature Research, 2023)
Piezoelectric nanogenerators (PENGs) have attracted great interest owing to their broad range application in environmental mechanical energy harvesting to power small electronic devices. In this study, novel flexible and high-performance double-layer sandwich-type PENGs based on one-dimensional (1-D) and two-dimensional (2-D) zinc oxide (ZnO) nanostructures and Ni foam as the middle layer have been developed. The morphology and structure of 1- and 2-D ZnO nanostructures have been studied by scanning electron microscopy (SEM) and X-ray diffraction (XRD). To investigate the effect of structural design on the piezoelectric performance, single-layer PENGs were also fabricated. The piezoelectric output of all prepared PENGs were evaluated under different human impacts at various forces and frequencies. The double-layer designed PENGs showed a two times larger voltage output compared to the single-layer PENGs, and the use of Ni foam as middle-layer and of 2-D ZnO nanosheets (compared to 1-D nanorods) was also found to increase the performance of the designed PENGs. The working mechanism of the prepared PENGs is also discussed. The design of nanogenerators as double-layer sandwich structures instead of two integrated single-layer devices reduces the overall preparation time and processing steps and enhances their output performance, thus opening the gate for widening their practical applications.